Movements and activities of white-lipped peccaries in Corcovado National Park, Costa Rica - Carrillo, Eduardo (2002)
The conservation of remnant populations of white-lipped peccaries in Central America depends on adequate documentation of their habitat needs and behavior. Thus, we monitored the activity patterns, local distributions, and home ranges of 36 (25F:11M) radio-marked white-lipped peccaries, all members of a single ‘‘super’’ herd, in part of Corcovado National Park, their largest stronghold in Costa Rica, during 1996–1998. Peccaries were diurnal all year with a period of reduced activity during the middle of the day. They were found more often than expected (vs. random use) in primary forest during February to May, in secondary and coastal forest during June to September, and in herbaceous swamp during October to January, corresponding to relative fruit abundance. Overall, the peccary herd ranged over an area of <40 km2 , but use of the area shifted seasonally and movements were reduced when fruit was most abundant. Our data agree with the suggestion that peccary density may be higher where the inter spersion or close proximity and mix of seasonally important habitats is high, and thus where peccaries do not have to travel as far for food. Habitat interspersion is therefore a significant conservation concern and should be addressed to make certain that peccary populations are not limited.